Yellow-Legged Hornet (suggested common name), Vespa velutina (Lepeletier 1836) (Insecta: Hymenoptera: Vespidae) - Krystal Ashman; Oliver Keller; Cameron Jack (EDIS, 2020)
The yellow-legged hornet, Vespa velutina (Lepeletier), is a pest of concern outside of its native range. Vespa velutina is native to Southeast Asia and has invaded several regions in Europe, first appearing in France in 2004. As a generalist predator, they are a pest of honey bees and a major concern to many beekeepers. Vespa velutina has not been intercepted in North America, but it is believed to have high invasion potential.